The Influence of the Mu'tazilah on Education in the Middle Century - Herlin Misliani; Munzir Hitami; Alpizar Alpizar (Edumaspul: Jurnal Pendidikan, 2022)
This research aims to determine the influence of the mu'tazilah school on education in the Middle Ages. This research method is a literature study. The results of the author's research based on various reference sources state that in the middle ages, namely during the Abbasid period, the educational achievements obtained at this time were extraordinary, especially in the mu'tazilah understanding. In the middle ages, namely during the Abbasid era, the mu'tazilah school had a strong influence on education so that the educational achievements obtained at this time were extraordinary. The Al-Mansur period was the period that became the beginning of the development of scientific achievements. Caliph Al-Mansur established a library as a storage place for ancient books and manuscripts, followed by Al-Rashid in developing this library and expanding the building both physically and functionally and named Bait Al-Hikmah. Caliph Al-Rashid restored the massive physical library building, and translated books and ancient manuscripts found in the library before and opened Bait Al-Hikmah open to teachers and Attorneys. Then during the reign of Al-Ma'mun, Caliph Al-Ma'mun appointed translators from Rome and bought ancient books in Rome. Caliph Al-Ma'mun also established a prominent research center near Bait Al-Hikmah called the Falak Tower or Observatory which is located in the area so that it does not only study theory but also proves the theory that has been studied. Caliph Al-Ma'mun also carried out extraordinary actions providing policies for translating large-scale works from Greece, India, Persia.